Enemies within the gates? : the Comintern and the Stalinist repression, 1934 - 1939 - Chase, William J. (Annals of communism, 2001)
"This work of documentary history tells a story of idealism betrayed, a story of how the Comintern (Communist International), an organization established by Lenin in 1919 to direct and assist revolutionary movements throughout the world, participated in and was ultimately destroyed by the Stalinist repression in the late 1930s. Presenting and drawing on recently declassified archival documents, William J. Chase analyzes the Comintern's roles as agent, instrument, and victim of terror."--BOOK JACKET.